Sex differences in the reactivity of gastric myoelectrical activity and heart rate variability as putative psychophysiological markers in human pain research - Rossitza Draganova; Genisius Hartanto; Robert Jan Pawlik; Jana Luisa Aulenkamp; Jana Luisa Aulenkamp; Sigrid Elsenbruch; Sigrid Elsenbruch (Frontiers in Neuroscience, 2024)
BackgroundThis study explored the potential of electrogastrography (EGG) and heart rate variability (HRV) as psychophysiological markers in experimental pain research related to the gut-brain axis. We investigated responses to the experience of pain from the visceral (rectal distension) and somatic (cutaneous heat) pain modalities, with a focus on elucidating sex differences in EGG and HRV responses.MethodsIn a sample of healthy volunteers (29 males, 43 females), EGG and ECG data were collected during a baseline and a pain phase. Data were analyzed for changes in gastric myoelectrical activity and cardiac autonomic regulation, with special attention to sex-specific patterns and correlations with perceptual responses to visceral and somatic pain stimuli, assessed by visual analogue scale ratings.ResultsAcute pain induced significant instability in EGG slow-wave frequency and amplitude, increased tachygastria, and decreased normogastric spectral power, without evidence of sex differences. HRV analyses revealed increases in SDNN, RMSSD, and pNN50 during pain, indicating sympathovagal regulation changes. While there were no significant sex differences in EGG responses, only female participants exhibited significant correlations between visceral pain unpleasantness and EGG alterations. HRV measures, particularly time-domain parameters, showed sex differences, independent of pain-induced autonomic reactivity.ConclusionThe experience of pain in the lower abdominal region may induce impaired gastric motility. EGG and HRV are sensitive to acute pain and offer insight into pain mechanisms along the gut-brain axis. While EGG responses were consistent across sexes, HRV revealed sex-specific differences, suggesting that autonomic regulation and gastric motility may be modulated differently by pain and psychosocial factors. Further research in patients with chronic visceral pain is warranted.